Using LiDAR Data and ArcGIS to Evaluate Subtle Glacial Landforms Associated with the Early Chippewa and Emeral Phase Ice-Margin Positions, Barron County, Wisconsin - Floyd, Corrie T. (My University, 2011)
The purpose of this study was to examine glacial landforms in Barron County, Wisconsin, which are the result of at least four glacial advances during the Pleistocene Epoch. During the early Chippewa and Emerald Phases, till of the Pokegama Creek and Poskin Members of the Copper Falls Formation were deposited over till of the River Falls Formation. High-resolution terrain models have been generated using LiDAR data to evaluate the Emerald Phase ice-margin proposed by M.D. Johnson in 1986.
Color poster with text, maps, graphs, and images.
Keywords: Geology--Computer programs; Geomorphology--Remote sensing; Glacial landforms--Wisconsin--Barron County; Glacial epoch--Wisconsin; Barron County (Wis.); Posters